C-terminal tyrosine removal from wheat low-molecular weight glutenin subunits (LMW-GS); biologically relevant or mistaken substrate?. (September 2020) - Bacala, Ray; Fu, Bin Xiao; Perreault, Hélène; Hatcher, Dave W.
Abstract: By applying a high-resolution LC-MS method, proteoform profiling of wheat glutenin proteins has revealed numerous protein pairs differing by an average mass of 163 ± 1 Da. The most abundant of 21 such pairs, 40 344 Da and 40 181 Da (coded P40344 and P40181, respectively), were purified and subjected to peptide mapping. P40344 matched the calculated mature protein mass for Uniprot B2Y2Q7, an s-type low-molecular weight glutenin subunit (LMW-GS). The P40344 and P40181 digests differed by a single digest peptide, unambiguously matched to the C-terminus of the protein and differing by the loss of a tyrosine. Of 327 unique mature wheat LMW-GS sequences from 369 UNIPROT accessions, tyrosine is at the C-terminus in all but one accession with evidence of transcription. The C-terminal LMW-GS sequences are also highly conserved, with only 10 variants of the last six amino acids. This is the first observation of cleavage of a C-terminal tyrosine other than alpha-tubulin, and the first evidence of this post-translational modification in plants. The identification of this novel post-translational modifications in gluten proteins may provide new insights on the differential modulation of biological processes involved in seed maturation and their effect on functional properties. Graphical abstract: Image 1 Highlights: 21 protein pairs differing by 0.3 min Rt and 163 Da found in wheat variety Cardale. Most abundant pair (P40344/P40186) matched Uniprot B2Y2Q7 (LMWGS) with 100% coverage. Pair differed by absence of C-terminal tyrosine, 100% conserved in expressed LMWGS. C-terminal tyrosine loss previously only observed for alpha-tubulin in mammals. First direct evidence of modification in plants.